Complexity of Participation Post-Stroke: Longitudinal Assessment of Community Participation, Positive Affect, Social Support and Functional Independence - Sameer A. Ashaie; Nichol Castro (Medical Journals Sweden, 2022)
Objective: To investigate longitudinal, predictive associations between community participation, positive affect, social support, and functional independence for individuals post-stroke at 3 and 12 months post-discharge. Design: Longitudinal design. Subjects: Data from 544 participants were obtained from the Stroke Recovery in Underserved Populations (2005-06) database. Methods: A cross-lagged panel network analysis to identify the complex set of predictive relationships between community participation, positive affect, social support, and functional independence 3 months post-discharge to 12 months post-discharge. Results: Community participation, particularly religious/spiritual activities, was an early predictor of later motor (functional) independence and social support. In addition, positive affect was an early predictor of social support. Conclusion: While participation in social situations is a desired outcome post-stroke, the results of this study indicate the importance of identifying early factors that influence community participation throughout the recovery process. LAY ABSTRACT The ability to participate in desired activities is a common outcome goal of rehabilitation for stroke survivors. However, there are many factors that influence success in achieving this goal, including support from family and friends, mental health, and functional independence. This study sought to understand how these factors influence each other and participation over time. The results indicate that early participation post-stroke is an important predictor of later motor independence and social support needs. The results indicate that, while participation is often viewed as a rehabilitation outcome, understanding participation as a predictor of other rehabilitation outcomes is also important.